Rural Settlement Network in Territory of Contemporary Omsk Region from Last Quarter of 19th Century to Early 20th Century - E. V. Sokolova (Научный диалог, 2023)
The article examines the characteristics of the formation of the rural settlement network in the territory of modern Omsk region during the last quarter of the 19th century through the early 20th century. The relevance of this study is driven by societal and governmental interest in rural history, as well as by the expansion of the source base, which is related to the popularization of museum collections and personal archives. Throughout the research, the author analyzes a wide range of sources and identifies features of the territory’s settlement, lifestyle, and everyday life of peasants, as well as the nature of relationships between settlers and natives. The author concludes that natural and geographical conditions played a significant role in shaping the network of rural settlements, organizing economic life, and the daily routines of peasants. Particular attention is paid to the study of the economic life of peasants, as it was one of the defining factors in the formation of the rural settlement network of the territory. The investigation reveals that agriculture was the main occupation for peasants in the Omsk Irtysh region, despite the limited amount of arable land available. Livestock breeding was confined to its economic significance. Additional income for peasants depended on their settlement location and was determined by the natural resources of the territory. Natural and geographical conditions also dictated the external appearance of settlements.